Gorham-Stout Disease Management during Pregnancy - Elena Bargagli; Caterina Piccioli; Edoardo Cavigli; Marianna Scola; Elisabetta Rosi; Federico Lavorini; Luca Novelli; Dario Ugolini; Tommaso Notaristefano; Pieralli Filippo; Vittorio Miele; Camilla E. Comin; et al. (Thieme Medical Publishers, Inc., 2017)
Gorham-Stout Disease (GSD) is a rare lymphatic disorder affecting children or young adults with no predilection of sex. It is generally associated with vanishing bone osteolytic lesions, thoracic and abdominal involvement, and diffuse pulmonary lymphangiomatosis. Chylous effusions and chylothorax, consequent to the abnormal proliferation of lymphatic vessels, may induce respiratory failure with a high mortality risk. Extrapulmonary alterations may include chylous ascites, lymphopenia, and destructing bone disease for overgrowth of lymphatic vessels. Here, we report the case of a young woman who developed a severe and recalcitrant GSD with persistent unilateral chylothorax during pregnancy. The complex management of this patient during and after pregnancy was discussed and compared with literature data to contribute to the definition of a correct diagnostic and therapeutic approach to this rare lymphatic disease.